2019
DOI: 10.1177/1049732319855967
|View full text |Cite
|
Sign up to set email alerts
|

Balance, Capacity, and the Contingencies of Everyday Life: Narrative Etiologies of Health Among Women in Street-Based Sex Work

Abstract: There is an abundance of health research with women in street-based sex work, but few studies examine what health means and how it is practiced by participants. We embrace these tasks by exploring how a convenience sample of sex workers ( n = 33) think about and enact health in their lives. Findings reveal pluralistic notions of health that include neoliberal, biomedical, and lay knowledge. Health is operationalized through clinic/hospital visits and self-care practices, which emerge as pragmatic behaviors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…However, PrEP awareness (Kuo et al, 2016; Shrestha et al, 2017; Stein et al, 2014) and uptake (Escudero et al, 2015; Stein et al, 2014; Walters et al, 2017) among people who inject drugs is low. Traditional methods of raising awareness about new HIV prevention modalities, such as education sessions during medical appointments, may not be ideal for reaching women who inject drugs, given barriers to health care utilization (Bungay, 2013; Heath et al, 2016; Luoma et al, 2007; Orchard et al, 2020), as well as PrEP prescription biases among health professionals toward patients with substance use disorders (Adams & Balderson, 2016; Edelman et al, 2017) and women (Pilgrim et al, 2018). Alternatively, research has shown that social networks can be organized to increase awareness and utilization of HIV prevention tools among people who inject drugs (Latkin, 1998; Theall et al, 2003; Tobin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, PrEP awareness (Kuo et al, 2016; Shrestha et al, 2017; Stein et al, 2014) and uptake (Escudero et al, 2015; Stein et al, 2014; Walters et al, 2017) among people who inject drugs is low. Traditional methods of raising awareness about new HIV prevention modalities, such as education sessions during medical appointments, may not be ideal for reaching women who inject drugs, given barriers to health care utilization (Bungay, 2013; Heath et al, 2016; Luoma et al, 2007; Orchard et al, 2020), as well as PrEP prescription biases among health professionals toward patients with substance use disorders (Adams & Balderson, 2016; Edelman et al, 2017) and women (Pilgrim et al, 2018). Alternatively, research has shown that social networks can be organized to increase awareness and utilization of HIV prevention tools among people who inject drugs (Latkin, 1998; Theall et al, 2003; Tobin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have addressed some of these topics, including unmet health care needs (Benoit et al, 2016a; Orchard et al, 2020), confidence in the police (Benoit et al, 2016b), views on Canada’s prostitution laws (Benoit et al, 2017a), self-esteem (Benoit et al, 2018), the impact of prostitution stigma at work and in personal lives (Benoit et al, 2019a, 2019c) and responses to prostitution stigma (Benoit et al, 2020). In another article based on a qualitative analysis of motivations for entering sex work, the authors found that participants identified three overlapping structural and agentic reasons for entry: critical life events, desire or need for money and personal appeal of the work.…”
Section: Methodsmentioning
confidence: 99%
“…The manner in which FSWs have encountered and been treated in health-care settings will inevitably play a key role in structuring their health-related behaviours and awareness. j INTERNATIONAL JOURNAL OF HUMAN RIGHTS IN HEALTHCARE j Many FSWs have experienced traumatic and stigmatising events from health-care professionals when accessing medical care (Orchard et al, 2020), fostering an untrustworthy and uninviting relationship between the two parties. Some FSWs have even indicated that negative experiences accessing sexual health services before entering the sex work industry have made them more skeptical to disclose their occupation to their health-care provider (Ryan and McGarry, 2022), and that if they do, medical staff have offered services to help enable their exit from the profession instead of sufficient care.…”
Section: Stigmatisation and Access To Health Carementioning
confidence: 99%